Co-Fe-Mo mixed metal oxides derived from layered double hydroxides for deep aerobic oxidative desulfurization. (15th December 2021) - Song, Ya; Bai, Jiabao; Jiang, Shenqin; Yang, Huawei; Yang, Lixia; Wei, Donglei; Bai, Liangjiu; Wang, Wenxiang; Liang, Ying; Chen, Hou
Graphical abstract: Highlights: Co-Fe-Mo oxides were constructed via the calcination of MoO4 2- intercalated LDH. Electronic structure of Mo can be regulated by altering the intercalation content. It showed outstanding performance in aerobic oxidation of thiophenic sulfides. The catalyst exhibited a prominent stability through the repeated experiments. Abstract: Aerobic oxidative desulfurization (AODS) is a vital development aspect for the deep desulfurization of fuel, which requires catalysts with high performance to efficiently convert thiophenic sulfides to sulfones. Here CoFeMo mixed metal oxides (MMOs) were synthesized through the calcination of molybdate (MoO4 2- ) intercalated CoFe layered double hydroxides (LDHs), which can serve as a robust and durable catalyst for AODS. The catalysts were synthetically characterized by using a range of techniques to identify its chemical and morphological properties, which showed that the content and electronic structure of Mo sites can be regulated by altering the intercalation content of MoO4 2-, and ultimately affect their catalytic performance. The optimal catalyst was capable of efficiently catalyzing the aerobic oxidative conversion of various thiophenic compounds into sulfones at 100 °C, and exhibited an excellent reusability by keeping the unchanged activity and chemical structure in repeated uses. This study would develop a feasible method to synthesize the highly efficient MMO catalysts for AODS of fuels.